Traffic noise and energy - R. Calejo Rodrigues (Energy Reports, 2020)
Urban noise depends on several factors from which Traffic Noise is the most important. City centers and main access roads are usually over exposed that is, average day-evening-night noise level [LDEN] and/or rest expose level [LNIGHT] surpasses a threshold of healthy exposure. About 35M Europeans are over exposed. This is a problem of human health not a comfort one. In another way, energy consumption associated to Urban Traffic is in the center of human concerns. Average vehicles spend more than 3.5MJ/km. That means that one Barrel of Oil Equivalent (BOE) is spent by Urban Traffic for each 1.700km. This is a problem of human sustainability. Based on this problematic a model was developed to correlate traffic noise reduction and energy savings in order to produce guidelines for Urban Noise Management. Model is supported on experimental data and bibliographic review, under the "CNOSSOS model for road noise". It is then possible to produce guidelines regarding noise reduction and its influence on energy savings. Relationships between "velocity reduction", "traffic volume" and "noise and energy" are now possible. Results are available in "noise maps" and "energy saving maps" easily understandable by urban traffic managers. A case study is presented.
Keywords: 330; CNOSSOS-EU; Sustainability; Traffic energy; Traffic noise